Infinitely iterated wreath products of metric spaces - Oliynyk, B. (Algebra and Discrete Mathematics, 2013)
The construction of the finitary wreath product of metric spaces and its completion, the infinitely iterated wreath product of metric spaces are introduced. They full isometry groups are described. Some properties and examples of these constructions are considered.